LITERATURE : ANALISIS GOING CONCERN, GREEN ECONOMY, INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN DENGAN MODERASI KEPEMILIKAN MANAJERIAL - Muhamad Fa'iz Paryono; Nera Marinda Machdar (Jurnal Ilmiah Akuntansi, 2026)
This article aims to analyze the conceptual relationship between Going Concern, Green Economy, and Intellectual Capital on Company Performance with Managerial Ownership as a moderating variable. This study employs a narrative literature review by synthesizing previous research to formulate hypotheses for future empirical investigations. The synthesis indicates that Green Economy and Intellectual Capital are positively associated with Company Performance, while the influence of Going Concern remains inconclusive. Managerial Ownership is identified as a potential moderating variable that may strengthen these relationships